Exploring Teacher Fairness in the Classroom: A Systematic Literature Review in Educational Psychology - Hazatriningrum Kusumawati; Farida kurniawati (Insight: Jurnal Ilmiah Psikologi, 2026)
Fairness in classroom assessment is a central issue in educational psychology because it shapes students’ motivation, trust, and engagement in learning. In contemporary classrooms, fairness is influencednotonlybytransparentassessmentproceduresbutalso by teacher–student interactions, cultural sensitivity, and digital learning conditions. This study aims to synthesize recent evidence on how teacher fairness is conceptualized and enacted in classroom assessment. A systematic literature review guided by thePICo framework(Population,Interest,Context)andreportedin accordance with the PRISMA guidelines was conducted using 15 peer-reviewed studies published between 2015 and 2025 and retrieved from major academic databases, including Google Scholar, ERIC, PsycINFO, JSTOR, Elsevier, Wiley, SAGE, Taylor & Francis, Springer Nature, PLOS, and Frontiers. The selected studies were analyzed using thematic analysis to identify recurring patterns, key dimensions, and contextual factors related to assessment fairness. The results show that teacher fairness consists of three interrelated dimensions: procedural, interpersonal, and distributive fairness. Procedural transparency and consistency are essential but insufficient without respectful interaction, constructive feedback, and equitable assessment outcomes.Thereviewalsoidentifiesclassroomassessmentliteracy and cultural sensitivity as key factors supporting fair assessment, especially in digital and post-pandemic learning environments. These findings contribute to educational psychology by offering an integrated understanding of fair classroom assessment and highlighting the need for continuous teacher professional development to promote inclusive, transparent, and responsive assessment practices